Genetic variation in MHC proteins is associated with T cell receptor expression biases - Sharon, Eilon; Sibener, Leah V; Battle, Alexis; Fraser, Hunter B; Garcia, K Christopher; Pritchard, Jonathan K (Nature genetics, 2016)
Jonathan Pritchard, Christopher Garcia and colleagues examine associations between different T cell receptor V genes and MHC alleles by eQTL mapping. They find that there are strong associations between MHC variation and T cell receptor gene usage and map these signals to specific MHC amino acids, many of which physically interact with germline-encoded amino acids on the T cell receptor. In each individual, a highly diverse T cell receptor (TCR) repertoire interacts with peptides presented by major histocompatibility complex (MHC) molecules. Despite extensive research, it remains controversial whether germline-encoded TCR–MHC contacts promote TCR–MHC specificity and, if so, whether differences exist in TCR V gene compatibilities with different MHC alleles. We applied expression quantitative trait locus (eQTL) mapping to test for associations between genetic variation and TCR V gene usage in a large human cohort. We report strong trans associations between variation in the MHC locus and TCR V gene usage. Fine-mapping of the association signals identifies specific amino acids from MHC genes that bias V gene usage, many of which contact or are spatially proximal to the TCR or peptide in the TCR–peptide–MHC complex. Hence, these MHC variants, several of which are linked to autoimmune diseases, can directly affect TCR–MHC interaction. These results provide the first examples of trans -QTL effects mediated by protein–protein interactions and are consistent with intrinsic TCR–MHC specificity.